Functional Group Structure of Bamboo and Pine Wood Biochar Due to Differences in Pyrolysis Temperature - Darusman Darusman; Syakur Syakur; Eka Kurniasih; Vera Puspita; Zaitun Zaitun (Graduate Program of Syiah Kuala University, 2022)
The quality of biochar produced through the pyrolysis process depends on the combustion temperature, duration of combustion, and the raw materials used. Biochar is a carbon-rich product resulting from the thermal decomposition of organic matter. Biochar from bamboo and pinewood was produced at 400℃ and 800℃ using a closed chamber where the temperature could be set. Biochar is made through carbonization with pyrolysis. This study aimed to find out the functional group characteristics of two types of raw materials, bamboo and pine wood. This research was conducted at the Environmental Soil Physics Laboratory, Universitas Syiah Kuala. Two types of feedstocks, bamboo, and pinewood, were used as sample experiments. The feedstocks were burned inside a closed chamber with no oxygen present. (Thermo scientific thermolyne F4820-33). The temperature was at 400℃ and 800℃, and a burning time of four hours. Fourier Transform Infra-Red (FTIR) was used to characterize the functional groups of biochar tested. Our research showed biochar from pinewood burned at a temperature of 400℃ gave the characteristics of the functional groups OH, CH, and C=O with strong intensity. It indicates that there was decomposition of organic matter into organic compounds taking place